Small Bowel Enteroscopy - Christopher W Teshima; Gary May (Canadian Journal of Gastroenterology)
Over the past decade, the advent of capsule endoscopy and balloon-assisted enteroscopy has revolutionized the approach to small intestinal diseases. The small bowel is no longer out of reach, and has fallen within the diagnostic and therapeutic realm of the gastrointestinal endoscopist. Double-balloon enteroscopy was the first type of balloon-assisted endoscopy and is the method for which there are the most data. Single-balloon enteroscopy has since been introduced as an alternative balloon-assisted method, followed more recently by the development of spiral overtube-assisted enteroscopy. The purpose of the present article is to review these methods of small bowel enteroscopy and to discuss the latest developments. While the investigation of small bowel diseases cannot be addressed without considering the central role of capsule endoscopy, a detailed assessment is beyond the scope of the present article, and capsule endoscopy will only be discussed as it pertains to enteroscopy.